Genomic and Physiological Characteristics of a Novel Nitrite-Oxidizing Nitrospira Strain Isolated From a Drinking Water Treatment Plant - Fujitani, Hirotsugu; Momiuchi, Kengo; Ishii, Kento; Nomachi, Manami; Kikuchi, Shuta; Ushiki, Norisuke; Sekiguchi, Yuji; Tsuneda, Satoshi (Frontiers in Microbiology, 2020)
Nitrite-oxidizing bacteria (NOB) catalyze the second step of nitrification, which is an important process of the biogeochemical nitrogen cycle and is exploited extensively as a biological nitrogen removal process. Members of the genus Nitrospira are often identified as the dominant NOB in a diverse range of natural and artificial environments. Additionally, a number of studies examining the distribution, abundance, and characterization of complete ammonia oxidation (comammox) Nitrospira support the ecological importance of the genus Nitrospira. However, niche differentiation between nitrite-oxidizing Nitrospira and comammox Nitrospira remains unknown due to a lack of pure cultures. In this study, we report the isolation, physiology, and genome of a novel nitrite-oxidizing Nitrospira strain isolated from a fixed-bed column at a drinking water treatment plant. Continuous feeding of ammonia led to the enrichment of Nitrospira-like cells, as well as members of ammonia-oxidizing genus Nitrosomonas. Subsequently, a microcolony sorting technique was used to isolate a novel nitrite-oxidizing Nitrospira strain. Sequences of strains showing the growth of microcolonies in microtiter plates were checked. Consequently, the most abundant operational taxonomic unit (OTU) exhibited high sequence similarity with Nitrospira japonica (98%) at the 16S rRNA gene level. The two other Nitrospira OTUs shared over 99% sequence similarities with N. japonica and Nitrospira sp. strain GC86. Only one strain identified as Nitrospira was successfully subcultivated and designated as Nitrospira sp. strain KM1 with high sequence similarity with N. japonica (98%). The half saturation constant for nitrite and the maximum nitrite oxidation rate of strain KM1 were orders of magnitude lower than the published data of other known Nitrospira strains; moreover, strain KM1 was more sensitive to free ammonia compared with previously isolated Nitrospira strains. Therefore, the new Nitrospira strain appears to be better adapted to oligotrophic environments compared with other known non-marine nitrite oxidizers. The complete genome of strain KM1 was 4,509,223 bp in length and contained 4,822 predicted coding sequences. Average nucleotide identities between strain KM1 and known cultured Nitrospira genome sequences are 76.7-78.4%, suggesting at least species-level novelty of the strain in the Nitrospira lineage II. These findings broaden knowledge of the ecophysiological diversity of nitrite-oxidizing Nitrospira.